Apropriação de práticas de letramentos ( e de numeramento ) escolares por estudantes da EJA - Fernanda Mauricio Simoes (2010)
In this work we analysed how young and grown-up Basical Education students learn schol practice of literary and numeracy. Those practices had been noticed in conversations between students and a Elementary Education teacher. This group studies at a public school from Belo Horizonte that offers Youth and Adult Education at night shift. The analyses had been done considering the concepts of literacy and numeracy, alphabetization and appropriation. We considered the cultural significance of reading and writing to understand the students behavior when they are practicing these skills. We tried to identify vallues, strategies and knowledges that students use to join human communication as knowledge and culture propitiator.